Physical fitness of highly qualified female and male wrestlers of various sports levels - Gierczuk, D.; Wójcik, Z. (Journal of Physical Education and Sport, 2023)
Research on studying fitness preparation in wrestling in the context of fighting style, gender and weight category can provide valuable tips for training work. There is a small number of scientific publications in which an attempt was made to determine the physical fitness of highly qualified female and male wrestlers. The deficit of scientific studies taking into account the fitness profile is particularly noticeable in women's wrestling. The aim of the study was to determine the physical fitness of female and male freestyle wrestlers (both men and women) of various levels of sports advancement. Highly qualified female and male freestyle wrestlers in the junior and senior age categories took part in the study. Due to body weight, the female and male competitors were divided into two conventional groups: light and heavy ones. The tests included the assessment of physical fitness, taking into account: explosive power, strength endurance, agility, flexibility and special endurance. The level of sports advancement, weight category and gender differentiate the physical fitness of highly qualified male and female freestyle wrestlers. Seniors of lightweight categories are characterized by higher values of special endurance than juniors of similar body weight. When divided into two weight categories, only in the case of male freestyle wrestlers in the senior category, differences in favor of competitors from lighter weight categories were visible in flexibility. Comparing physical fitness by gender, men dominated in explosive power, strength endurance, agility and special endurance, however women dominated in flexibility. The physical fitness of highly qualified female and male wrestlers varies according to the level of sports advancement, gender and weight category. Training groups at various stages of sports advancement should be created according to gender and weight category. In the motor preparation of female and male wrestlers of all weight categories, the leading components of physical fitness different for a particular gender should be emphasized in the first place. This should be taken into account in the selection of training measures aimed at specific components of physical fitness among female and male wrestlers.